1970
DOI: 10.1139/m70-079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radiation pasteurization on Salmonella. I. Parameters affecting survival and recovery from chicken

Abstract: Growth of Salmonella typhimurium, strain RIA, in minimal broth supplemented with methionine, produced a population of cells that was more sensitive to 60Co irradiation than were those grown in brain heart infusion. The resistance values (D) were 0.056 and 0.066 Mrad, respectively. D was not significantly different when the bacteria were irradiated at 4 °C on fresh or frozen-thawed germ-free chicken, or on conventional chicken sterilized by autoclaving, or by exposure to 2 Mrad of ionizing radiation. It was gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1979
1979
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Effect of frozen state on the radiation resistance of Y. enteroolitica. The radiation resistance of vegetative bacteria is usually two to five times greater in the frozen state than in the nonfrozen state (1, 4, 10,19,23 Effect of the suspending medium on the radiation resistance of Y. enterocolitica (strain IP107) at 25°C. A straight line was fitted as in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Effect of frozen state on the radiation resistance of Y. enteroolitica. The radiation resistance of vegetative bacteria is usually two to five times greater in the frozen state than in the nonfrozen state (1, 4, 10,19,23 Effect of the suspending medium on the radiation resistance of Y. enterocolitica (strain IP107) at 25°C. A straight line was fitted as in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated irradiation temperatures significantly reduce the survival of Salmonella and subfreezing temperatures during irradiation increase survival (Licciardello 1964;Previte et al 1970). Salmonella typhimurium cells surviving low doses of gamma radiation are more sensitive to heat than nonirradiated cells, and thus are unlikely to survive even a mild cooking process (Thayer ef al.…”
Section: Introductionmentioning
confidence: 99%
“…A similar reduction in cell numbers was achieved with Salmonella in fresh poultry (12,18) and several enteropathogenic strains of Y. enterocolitica of known human etiology (7). Furthermore, several reports indicated that low temperatures during irradiation significantly affected the results of radiation on bacterial cells (2,6,7,13,19,20). Freezing and frozen storage either alone or in combination with radiation resulted in a distinct enhancement of cell inactivation and injury of gramnegative bacteria, including Y. enterocolitica (4,7,10).…”
mentioning
confidence: 62%